EXPLORING 7TH-GRADE JUNIOR HIGH SCHOOL STUDENTS' PERCEPTIONS OF USING THE ELSA SPEAK APP IN MALL-BASED PRONUNCIATION LEARNING - Malya Anisa Estiningtyas; Abdul Kodir Al-baekani; Praditya Putri Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the learning process at the junior high school level, English pronunciation remains an under-appreciated component, particularly in Indonesia. However, good pronunciation is crucial for effective communication. This study aims to investigate how seventh-grade students with low pronunciation skills perceive the use of the ELSA Speak app in MALL. This research employed a qualitative approach, specifically designed as a case study. Data were collected from five seventh-grade students at a junior high school in Karawang through participant observation, direct use of the ELSA Speak app, and semi-structured interviews. The results indicate that the use of ELSA Speak provides significant benefits in helping pronunciation skills, building student confidence, and increasing motivation for independent learning. However, several technical challenges and limitations in vocabulary comprehension were also identified. These findings demonstrate the great potential of ELSA Speak as an innovative and effective pronunciation learning medium at the junior high school level.